2007
DOI: 10.1007/bf02913313
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of glycemic potential ofMusa paradisiaca stem juice

Abstract: The present study reveals the effect of Musa paradisiaca stem juice on blood glucose level (BGL) Address for Correspondence :Dr. Geeta Watal Alternative Therapeutics Unit, Drug Development Division, Medicinal Research Lab, Department of Chemistry, University of Allahabad, Allahabad -211002 E-mail : geetawatal@gmail.com banana fruit pulp to treat ulcers have been explored by a number of investigators (9-12). Since, the flowers and the roots of Musa sapientum showed hypoglycemic effect on normal fasting rabbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…The precise mechanism of action by which MEMP does this is still unclear. Musa paradisiaca has hypoglycaemic effects in both normal and diabetic animal models, and this might be a reason for its ability to facilitate improvement in male sexual functions in diabetic animals 10202324. This is true when the mature green fruit of plantain is consumed at a moderate dose, as revealed in the current study, where consumption of Musa paradisiaca at a low dose led to improvement in the quantity and quality of spermatozoa in adult Wistar rats.…”
Section: Discussionsupporting
confidence: 55%
“…The precise mechanism of action by which MEMP does this is still unclear. Musa paradisiaca has hypoglycaemic effects in both normal and diabetic animal models, and this might be a reason for its ability to facilitate improvement in male sexual functions in diabetic animals 10202324. This is true when the mature green fruit of plantain is consumed at a moderate dose, as revealed in the current study, where consumption of Musa paradisiaca at a low dose led to improvement in the quantity and quality of spermatozoa in adult Wistar rats.…”
Section: Discussionsupporting
confidence: 55%
“…Dwarf Cavendish) indicate its potential application as a source of functional food products (Oliveira et al 2008). A separate study done by Singh et al (2007) revealed that oral administration of banana pseudostem juice (Musa paradisiaca) to the normal and hyperdiabetic (high glucose level in blood) rats shows a significant increase of blood glucose level, signify a possible treatment hypoglycemic patients due to low insulin level or hypoglycemic drugs.…”
Section: Source Of Nutraceutical and Bioactive Compoundsmentioning
confidence: 97%
“…elakki bale banana flower [15], M. sapientum Linn. stem juice [16], Musa paradisiacal stem juice [17], Musa sp. var.…”
Section: Introductionmentioning
confidence: 99%